THE POWER OF LITERARY WORKS IN BUILDING YOUNG ENTREPRENEUR'S CHARACTER AS REFLECTED IN BUYA HAMKA'S FICTION - Octaviyanti, Cindy Kurnia (UNISSULA, 2017)
War, poverty, hunger, and health issues still remain big problems in global era. Facing an era like today, the youth can not only sit and wait for chance to come to them. Preparing the youth is one of the ways to overcome the problems. This idea is recognized by the youths themselves and has awakened an awareness to build leader characters since the very first time. There are several ways to create the leader characters and one and the most important of them is by modeling. This paper discusses how Buya Hamka’s fiction can serve as leader model for youths to be a successful entrepreneur. Through his influential literary works, Buya Hamka has introduced and exemplified the youths to face an era like today. This paper uses descriptive qualitative approach which identified the power of literary works in leading the world as seen in Buya Hamka. The data for analysis were collected by library research. Even though Buya Hamka lived in the past, his spirit and ideas are still alive and relevant that young people can adopt in the present time. Buya Hamka is an exemplary and inspiring entrepreneur who had devoted his life for people, the nation and the change of a better world.Keywords: Buya Hamka, leader characters, youth, literary work.